Epigallocatechin gallate inhibits urate crystals-induced peritoneal inflammation in C57BL/6 mice - Jhang, Jhih-Jia; Lu, Chi-Cheng; Yen, Gow-Chin (Molecular nutrition & food research, 2016)
Gouty arthritis is a type of monosodium urate (MSU) crystals‐induced inflammation in the articular tissue and shows the increased levels of neutrophil infiltration and IL‐1β secretion. MSU is capable of activating IL‐1β through a nucleotide‐binding oligomerization domain‐like receptor containing pyrin domain 3 (NLRP3) inflammasome. Epigallocatechin gallate (EGCG), a bioactive polyphenol in green tea with potent antioxidant activity, is effective to prevent rheumatoid arthritis and osteoarthritis. However, it remains unclear whether EGCG improves gouty inflammation. This study aimed to investigate the effect of EGCG on MSU‐induced inflammation and NLRP3 inflammasome activation. C57BL/6 mice were received subcutaneous injection or oral gavage of EGCG before the intraperitoneal injection of MSU. The results demonstrated that EGCG inhibited MSU‐induced neutrophil infiltration and IL‐1β secretion. Furthermore, EGCG decreased MSU‐triggered neutrophil cytosolic factor 1 and NLRP3 protein expression, limiting pro‐inflammatory mediator secretion such as IL‐1β, IL‐6, monocyte chemoattractant protein‐1, and serum amyloid A. In addition, EGCG treatment suppressed NLRP3 inflammasome activation in MSU‐challenged THP‐1 monocytes. These findings indicate that EGCG treatment ameliorates MSU‐induced inflammation, suggesting that EGCG exerts anti‐inflammatory effect against MSU‐induced acute gout attack. The protective effect of EGCG on MSU‐induced inflammation is studied. MSU induced inflammation in C57BL/6 mice and THP‐1 cells. EGCG ameliorates MSU‐induced neutrophil infiltration and proinflammatory cytokine secretion in C57BL/6 mice. EGCG also inhibits MSU‐triggered NLRP3 inflammasome activation and oxidative stress in THP‐1 cells.